$2\displaystyle\int_0^\pi \sin x + \sin x \cos x\,dx$

I let $u=\sin x \implies \dfrac{du}{dx}=\cos x \implies dx=\dfrac{du}{\cos x}$

$2\displaystyle\int_{x=0}^{x=\pi} 2u\,du$

When I try to change the limits I just get 0 and 0: Lower limit $=\sin 0 = 0$, upper limit $=\sin \pi=0$

$2\left[u^2\right]^0_0 = 0$. The answer should be 4, not 0.


  • $\begingroup$ What about zeros of $\cos x$ when you deal with $\frac{\mathrm du}{\cos x}$? Why don't you go with the classical $u = \tan\frac x2$? $\endgroup$ – Ilya Apr 4 '13 at 9:30
  • $\begingroup$ You seem to have forgotten to divide the $\sin x$ term by the $\cos x$ obtained from the substitution. Also, $\sin$ is not bijective on $(0,\pi)$ rendering the application of the substitution theorem invalid. If you want to solve by substitution, it's probably best to split the integration interval into $(0,\pi/2)$ and $(\pi/2,\pi)$. $\endgroup$ – Lord_Farin Apr 4 '13 at 9:36

Assuming the question is : $2\int_{0}^{\pi}(sin(x) + sin(x)cos(x))dx$

It is not 2$\int_{0}^{\pi} 2u. du$ on simplification.

It is 2$\int_{0}^{\pi} udx + udu$

Instead of substituting, you can just divide the integration into two and proceed as follows:

$$=2\int_{0}^{\pi}sinx .dx + \int_{0}^{\pi} sin(2x).dx $$

$$=2(-cos(x)) + \dfrac{(-cos(2x))}{2}$$ Then apply the limit from $0$ to $\pi$:

$$=2(1-(-1)) + 0$$


Hope the answer is clear !

  • $\begingroup$ Now I get it, thank you very much! $\endgroup$ – Hans Groeffen Apr 4 '13 at 9:48

As $$\int_a^b f(x)dx=\int_a^b f(a+b-x)dx$$

If $f(x)=\sin x+\sin x\cos x,$ $f(\pi+0-x)=\sin(\pi+0-x)+\sin(\pi+0-x)\cos(\pi+0-x)=\sin x-\sin x\cos x$ as $\sin(\pi-x)=\sin x,\cos(\pi-x)=-\cos x$

So, $$\int_0^\pi (\sin x + \sin x \cos x)dx=\int_0^\pi (\sin x - \sin x \cos x)dx=I\text{ say}$$

So, $$2I=\int_0^\pi (\sin x + \sin x \cos x)dx+\int_0^\pi (\sin x - \sin x \cos x)dx=2 \int_0^\pi\sin xdx$$

So, $$I=\int_0^\pi\sin xdx=(-\cos x)|_0^\pi=-\cos\pi-(-\cos 0)=2$$

Alternatively, $$\int_0^\pi (\sin x + \sin x \cos x)dx=\int_0^\pi \left(\sin x +\frac{\sin2x}2\right)dx=\left(-\cos x -\frac{\cos2x}4\right)_0^\pi$$

$$=\left(\cos x +\frac{\cos2x}4\right)_\pi^0=\cos0+\frac{\cos0}4-\left(\cos\pi+\frac{\cos\pi}4\right)=1+\frac14-\left(-1+\frac14\right)=2$$

In fact, $\int_0^\pi\sin2xdx=\int_0^{2\pi}\sin ydy=(-\cos y)_0^{2\pi}=1-1=0$


You lost the first summand there.

$$ 2\int_0^\pi \sin x + \sin x \cos x\,dx = 2\int_0^\pi \sin x\,dx + 2\int_0^\pi \sin x \cos x\,dx $$ Now integrate both summands separately; you don't need to substitute in the first.

  • $\begingroup$ Even if you are in a class and there is a current subject, you should be ready to use other techniques, or you should realize that the current subject applies only partially. $\endgroup$ – Eric Jablow Apr 5 '13 at 1:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.